Brand Perceptions and the Market for Common Stock - Frieder, Laura; Subrahmanyam, Avanidhar (Journal of Financial and Quantitative Analysis, 2005)
Abstract This paper investigates the effect of company brand perceptions on investor propensities to hold stocks. We find that, after controlling for other determinants of stockholdings, there is a negative and significant cross-sectional relation between institutional holdings and brand visibility, which is consistent with the notion that individual investors prefer to invest in stocks with easily recognized products. Furthermore, we find that institutional holdings are positively related to firm size and beta. Our analysis supports the notion that institutional portfolios eschew relatively neglected small firms, whereas individuals prefer holding stocks with high recognition and, consequently, greater information precision.